Layered double hydroxide-functionalized humic acid and magnetite by hydrothermal synthesis for optimized adsorption of malachite green - Nur Ahmad; Alfan Wijaya; Fitri Suryani Arsyad; Idha Royani; Aldes Lesbani (Kuwait Journal of Science)
The present study uses the hydrothermal method to prepare nickel aluminum layered double hydroxide-functionalized humic acid and magnetite. Scanning electron microscopy, Fourier transfer infra-red, X-ray diffraction, N2 adsorption-desorption isotherm, and vibrating sample magnetometer measurements are also used to determine the adsorbent's physicochemical properties. The mesopore-filling activity of Ni/Al functionalized humic acid and magnetite facilitates malachite green adsorption. Ni/Al functionalized humic acid and magnetite was collected from the water solution with a small additional magnet. Ni/Al and Ni/Al functionalized humic acid and magnetite exhibited type-IV sorption isotherms with the surface area of Ni/Al quadruples following functionalization with humic acid and magnetite. The pseudo-second-order kinetic and Langmuir isotherm adequately describe the adsorption process of the batch system. In the current case, the interaction of humic acid, magnetite, and the Ni/Al component may impact the leaching kinetics. Various factors, including pH, temperature, and competing ions, can impact the release of malachite green from the adsorbent surface. Malachite green has maximal Langmuir adsorption capacities of 68.966 mg/g and 178.571 mg/g on Ni/Al and Ni/Al-functionalized humic acid and magnetite, respectively. The result of the physisorption interaction processes was its efficient adsorption capacity for malachite green. This study offered recommendations on the development of adsorbents with high efficiency for the adsorption of malachite green.